Articulações estéticas entre narrativas literárias e imagéticas: a escravidão em uma perspectiva histórica. - Jeissyane Furtado da Silva (Nepan editor, 2021)
This article aims to reflect on literary and imagery aesthetics, as linguistic forms focusing on slavery. Among the analyzed productions, we propose a debate that surrounds the issues of gender and race from a theoretical-comparative basis of the images of Jean-Baptiste Debret (1818, 1822, 1827, 1835), Henry Chambertain (1830), Francis Meynell (1845) and Tarsila do Amaral (1930), and also the letters of Maria Firmina dos Reis (2018), Angela Davis (2016), Eduardo de Assis Duarte (2017), Sidney Chalhoub (2018), Herbert Klein (2018) and Keila Grinberg (2018). We dialogue with perspectives that focused on discussing the supossed condition of inferiority and the representation of the black, inserted in a logic of power and control over the other.